2014
DOI: 10.1088/1748-9326/9/2/024016
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide and fertilizers promote analogous phylogenetic responses but opposite functional responses in plant communities

Abstract: Throughout the world, herbicides and fertilizers change species composition in agricultural communities, but how do the cumulative effects of these chemicals impact the functional and phylogenetic structure of non-targeted communities when they drift into adjacent semi-natural habitats? Based on long-term experiment we show that fertilizer and herbicides (glyphosate) have contrasting effects on functional structure, but can increase phylogenetic diversity in semi-natural plant communities. We found that an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
2
17
1
1
Order By: Relevance
“…This study also revealed that leaf width, leaf chlorophyll and N concentrations, SLA, and single leaf wet weight of R. typhina increased in the presence of all N fertilizers; medium N and high N also increased leaf length and leaf thickness of R. typhina (Table 1). The result is consistent with our hypothesis and previous studies [15,32]. This implied that R. typhina leaves may possess higher resource capture ability as well as higher relative growth rate with reduce material investment per unit area under exogenous N fertilization.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study also revealed that leaf width, leaf chlorophyll and N concentrations, SLA, and single leaf wet weight of R. typhina increased in the presence of all N fertilizers; medium N and high N also increased leaf length and leaf thickness of R. typhina (Table 1). The result is consistent with our hypothesis and previous studies [15,32]. This implied that R. typhina leaves may possess higher resource capture ability as well as higher relative growth rate with reduce material investment per unit area under exogenous N fertilization.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, plants can present stimulated growth and physiological performance under elevated N supply mainly via eliminating N defi ciency [9][10]. Generally, N fertilization could increase leaf size, leaf chlorophyll and N concentrations, and SLA [15,32]. This study also revealed that leaf width, leaf chlorophyll and N concentrations, SLA, and single leaf wet weight of R. typhina increased in the presence of all N fertilizers; medium N and high N also increased leaf length and leaf thickness of R. typhina (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Inference about the consequences of PNC on functional composition (CWM) has been usually made indirectly via estimates of phylogenetic signal in traits (e.g. Cavender-Bares and Reich 2012, Pellissier et al 2014), mostly using the K statistic (Blomberg et al 2003, Cooper et al 2010. PNC assessment via phylogenetic signal estimates has been a topic of heated debate over the last decade (Losos 2008, Wiens 2008.…”
Section: From Trait Evolution Models To Functional Composition and Backmentioning
confidence: 99%
“…Het gebruik van herbiciden op grasland ter beheersing van (on)kruiden leidt tot een verarming van de botanische samenstelling van grasland, wat resulteert in een lagere ondergrondse en bovengrondse biodiversiteit. De drift van herbiciden naar aangrenzende habitats zorgt daar ook voor veranderingen in biodiversiteit (Pellissier et al, 2014). Als herbiciden echter gebruikt worden als onderhoudsmaatregel om graslandvernieuwing door middel van herinzaai te voorkomen, dan zijn ze te prefereren boven het scheuren van grasland.…”
Section: G N-bodemoverschot Per Haunclassified